PENGARUH KETERLIBATAN PEMAKAI, KOMPLEKSITAS TUGAS DAN DUKUNGAN MANAJER TERHADAP EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI PADA KOPERASI SIMPAN PINJAM DI KECAMATAN DENPASAR SELATAN - Ni Kadek Dwi Lestari Putri; I Putu Fery Karyada (UNHI Press, 2020)
The accounting information system helps in terms of making external reports, supporting routine activities, supporting decision making, planning and controlling and implementing internal control. The effectiveness of accounting information systems can be influenced by a number of factors including: the involvement of users or employees who use accounting information systems, the complexity of the work done by employees, and the support of top management. The purpose of this study was to examine the effect of user involvement, task complexity, and top management support on the effectiveness of the use of accounting information systems in Saving and Credit Cooperatives in South Denpasar District. The population used in this study were all Savings and Loan Cooperative employees in the South Denpasar District of 285 people. Determination of the sample using purposive sampling so that 83 people were obtained as samples. After testing the instrument and testing the classic assumptions, then data analysis is performed using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that the influence of user involvement on the effectiveness of the application of accounting information systems obtained a regression coefficient of 0.678, a t-test value of 8.831 and a significant value of the t test of 0.000 <0.05, so H1 was accepted. The effect of task complexity on the effectiveness of applying the accounting information system obtained a regression coefficient of -0.261, a calculated t value of -2.069 and a significant value of t test of 0.042 <0.05, so H2 was accepted. The influence of top management support on the effectiveness of the application of accounting information systems obtained a regression coefficient of 0.451, a calculated t value of 2.636 and a significant value of t test of 0.010 <0.05, so that H3 is accepted. It is suggested to cooperatives to keep trying to develop and implement a better and quality accounting information system.